Pasantía En El Ministerio De Comercio Industria Y Turismo - Mora Valencia, Angélica María (Universidad Antonio Nariño, 2022)
The purpose of this report is to be able to share this learning experience with all those students who are interested in carrying out their work internship in an entity such as the public sector, which allows consolidating the knowledge acquired by the institution and being a first instance to the professional exercise of the International Trade career. This internship was carried out in a period of six months between April and October 2021, in the MINISTRY OF TRADE, INDUSTRY AND TOURISM. The internship was developed in the Directorate of Economic Integration, on the subject of the Andean Community Trade Agreement, specifically focused on supporting the implementation of processes and activities carried out in the exercise of the Pro Tempore Presidency in the CAN that Colombia led during this year. Carrying out these activities made it possible to strengthen the knowledge acquired at the University and develop greater capacities to face the labor field. The main results are related to updating technical, administrative and commercial information, establishing dynamic and direct relationships